Occurrence of intracranial large vessel occlusion in consecutive, non-referred patients with acute ischemic stroke. Issue 1 (December 2016) - Beumer, Debbie; Mulder, Maxim; Saiedie, Ghesrouw; Fonville, Susanne; van Oostenbrugge, Robert; van Zwam, Wim; Homburg, Philip; van der Lugt, Aad; Dippel, Diederik
Abstract Background The relative frequency of acute intracranial large vessel occlusion (LVO) in patients with acute ischemic stroke (AIS) who could be candidate for intra-arterial treatment (IAT) is not well known. In this study, we determined clinical variables associated with LVO and the proportion of patients with LVO among patients presenting with AIS within 6 h of symptom onset. Methods Data of consecutive patients with AIS presenting at the emergency department (ED) of the Erasmus University Medical Center, in the Netherlands, was used. Referrals from other hospitals were excluded. Results From 2006 January 1st to 2012 April 30th, 1063 non-referred patients presented at our ED with AIS. 445 (42 %) arrived within 6 h of onset of symptoms. Computed tomography angiography was not performed or was of insufficient quality in 50 patients (11 %) and performed late (≥1 day) in 57 patients (13 %). The remaining 338 with AIS were included in the final analysis. 106 patients (31 %) had LVO, mostly in the anterior circulation (72 %). National Institutes of Health Stroke Scale score was the only variable associated with the presence of LVO (adjusted OR 1.23 per point [95 % Confidence interval: 1.17–1.29]). Conclusion Of all patients with acute ischemic stroke who arrive within 6 h of symptom onset at the emergency department, almost one out of three have a intracranial large vessel occlusion and may be candidate for intra-arterial treatment.